Solving conflicting believes with a distributed belief revision approach - Eugénio Oliveira (2000)
The ability to solve conflicting beliefs is crucial for multi-agent systems where the information is dynamic, incomplete and distributed over a group of autonomous agents. The proposed distributed belief revision approach consists of a distributed truth maintenance system and a set of autonomous belief revision methodologies. The agents have partial views and, frequently, hold disparate beliefs which are automatically detected by system's reason maintenance mechanism. The nature of these conflicts is dynamic and requires adequate methodologies for conflict resolution. The two types of conflicting beliefs addressed in this paper are context dependent (CD) and context independent (CI) conflicts which result, in the first case, from the assignment by different agents of opposite belief statuses to the same belief, and, in the latter case, from holding contradictory distinct beliefs. The belief revision methodology for solving CI conflicts is, basically, a selection process based on the assessment of the credibility of the opposing belief statuses. The belief revision methodology for solving CD conflicts is essentially a search process for a consensual alternative based on a ldquonext bestrdquo relaxation strategy.